Market driven by sustainable construction and demolition waste in UAE - GERNAL, M.L; SERGIO, R.P; MUSLEH, A.J (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper aims to evaluate the regulations in the United Arab Emirates (UAE) treatment plant, and its market-driven acceptability of using construction and demolition waste (CDW). This research paper highlights the exceptional work of the 10 construction companies in the UAE in their operational achievements as turnaround after the recession.  Effective strategies helped businesses during this period including the expansion into crisis-resistant markets such as acceptability of the market to use CDW; introducing market lines; maintaining prices while augmenting existing products; developing adaptive positioning; using informative advertisements; and pruning marginal channels.